2020
DOI: 10.1083/jcb.202002154
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive collaboration between integrins and connexins allows nutrient and antioxidant transport into the lens

Abstract: The delivery of glucose and antioxidants is vital to maintain homeostasis and lens transparency. Here, we report a new mechanism whereby mechanically activated connexin (Cx) hemichannels serve as a transport portal for delivering glucose and glutathione (GSH). Integrin α6β1 in outer cortical lens fiber activated by fluid flow shear stress (FFSS) induced opening of hemichannels. Inhibition of α6 activation prevented hemichannel opening as well as glucose and GSH uptake. The activation of integrin β1, a heterodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…Gap junction proteins play an important role in lens homeostasis and transparency [ 3 5 , 11 25 , 65 67 ]. They are responsible for transporting small molecular nutrients and metabolites [ 11 18 , 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gap junction proteins play an important role in lens homeostasis and transparency [ 3 5 , 11 25 , 65 67 ]. They are responsible for transporting small molecular nutrients and metabolites [ 11 18 , 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gap junction proteins play an important role in lens homeostasis and transparency [ 3 5 , 11 25 , 65 67 ]. They are responsible for transporting small molecular nutrients and metabolites [ 11 18 , 24 25 ]. More recently, Liu et al [ 21 ] elegantly demonstrated that these gap junction proteins are also capable of delivering antioxidants and maintaining the redox status of the ocular lens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations